Customer Behavior and EV Charging Service Business - Mangunkusumo, K.G.H.; Irnawan, R.; Widhyharto, D.S.; Usman, S.; Sarjiya, Sarjiya; Putranto, L.M.; Muthohar, I.; Haryadi, F.N. (Institute of Electrical and Electronics Engineers Inc., 2021)
The transportation sector in Indonesia is estimated to absorb more than 50 of the total national fuel consumption. One form of fuel saving effort carried out by PLN (Indonesia's electricity company) is to encourage the growth of battery-based electric vehicles (EV). On the other hand, a strategy of adding electrical loads is needed to absorb underutilized power plants and increase the percentage of annual load growth. Electricity charging infrastructure for EV is an alternative solution to solve these problems. In this study, cluster sampling and purposive sampling methods were used. Furthermore, in order to improve the comprehensiveness of the research, a Focus Group Discussion (FGD) was conducted by involving the government, experts, observers, and transportation business actors as well as corresponding PLN Units. From the result, it is known that important aspects in the development of public electric vehicle charging stations (SPKLU) are: designation, development, and governance, its locations, and payment systems. SPKLU business development needs to pay attention to driving behavior (mobility and driving time) which forms a monocentric and polycentric pattern, i.e. correlated with the driving anxiety factor. Optimizing the functions of these aspects for SPKLU businesses must be supported by stakeholder engagement (participation of the government, PLN, investors, implementing contractors, and suppliers), good governance, and customer adaptability. Â© 2021 IEEE.